Antibacterial and Cell-Viability of Hydroxyapatite Derived from Waste Marine Shell for Biomedical Applications - Suresh, G.; Dhanaraj, K.; Viswanath, R.N.; Dhanalakshmi, B.; Sindhya, A. (Asian Journal of Chemistry, 2024)
The present study discusses on the functional groups, structural characterization and thermal behaviour of Crassostrea angulata shell used for the synthesis of a biocompatible hydroxyapatite material. The hydroxyapatite was synthesized from C. angulata shell through precipitation method and characterized using XRD, FTIR, FE-SEM, EDX mapping, HR-TEM and SAED pattern. The formation of hydroxyapatite was confirmed from the high intense X-ray diffraction lines and by the presence of chemical groups such as PO43–, OH– and CO32–. The structural changes during the formation of hydroxyapatite from the thermal decomposition of C. angulata shell were studied through XRD and TG-DTA. The morphology study by FE-SEM indicates that the synthesized hydroxyapatite materials were in the form of clusters of rod-like particles. The SAED patterns and XRD spectral lines confirmed the crystalline nature of the synthesized hydroxyapatite. The antibacterial activity and cell viability assay of prepared hydroxyapatite were studied to assess its suitability in various biomedical applications. The antibacterial activity of hydroxyapatite was assessed against Gram-negative (Escherichia coli) and Gram-positive (Staphylococcus saprophyticus) bacterial strains. The cytocompatibility of hydroxyapatite was assessed through an MTT assay using osteoblast cells (MG-63 cell). Thus, the prepared hydroxyapatite shows good antibacterial action and cell viability nature and it can be applied in various biomedical applications.